2018
DOI: 10.1111/jsr.12682
|View full text |Cite
|
Sign up to set email alerts
|

Associations between self‐reported sleep measures and dietary behaviours in a large sample of Australian school students (= 28,010)

Abstract: This study examined the associations between self-reported sleep timing and quality, and the frequency of breakfast and junk food consumption in 28,010 Australian school students (mean ± SD age = 13.3 ± 1.2 years, 51% male). After controlling for age, sex and socioeconomic status, regression analyses revealed that the odds of missing breakfast were significantly higher in children who reported poor sleep or later bedtimes, while the odds of junk food consumption were significantly higher in children reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 24 publications
(37 reference statements)
7
28
0
1
Order By: Relevance
“…Numerous studies identified several risk factors that associate with sleep insufficiency, including gender, older age, higher body mass index and waist circumference and unhealthy lifestyle habits such as physical inactivity, high screen viewing and dietary choices 1,1520. However, not many studies have examined the association of sleep duration with skipping breakfast among children and adolescents 19,21,22. One study showed that after controlling for age, sex and socioeconomic status, sleep timing and quality had influenced the dietary choices of a large number of Australian school children and adolescents, as those who missed breakfast reported significantly poorer sleep 21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies identified several risk factors that associate with sleep insufficiency, including gender, older age, higher body mass index and waist circumference and unhealthy lifestyle habits such as physical inactivity, high screen viewing and dietary choices 1,1520. However, not many studies have examined the association of sleep duration with skipping breakfast among children and adolescents 19,21,22. One study showed that after controlling for age, sex and socioeconomic status, sleep timing and quality had influenced the dietary choices of a large number of Australian school children and adolescents, as those who missed breakfast reported significantly poorer sleep 21.…”
Section: Introductionmentioning
confidence: 99%
“…However, not many studies have examined the association of sleep duration with skipping breakfast among children and adolescents 19,21,22. One study showed that after controlling for age, sex and socioeconomic status, sleep timing and quality had influenced the dietary choices of a large number of Australian school children and adolescents, as those who missed breakfast reported significantly poorer sleep 21. Among a large sample of Greek children and adolescents aged 8–17 year-olds, insufficient sleep duration was associated with unhealthy dietary habits including skipping breakfast 19.…”
Section: Introductionmentioning
confidence: 99%
“…Eating an unhealthy diet impairs the mental and physical health of a person. 70 Eating unhealthy food also causes sleep problems. 71 On the other hand, in underdeveloped countries, low SES can also cause problems tied to being underweight.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was observed that individuals who did not have regular breakfast had poorer sleep quality. However, not many studies have examined the association of sleep duration with skipping breakfast among adolescents [51][52][53] . Among a large sample of Greek children and adolescents, insufficient sleep duration was associated with unhealthy dietary habits including skipping breakfast 51 .…”
Section: <001 [A-bc][b-c]mentioning
confidence: 99%
“…Among a large sample of Greek children and adolescents, insufficient sleep duration was associated with unhealthy dietary habits including skipping breakfast 51 . One study showed that skipping breakfast were significantly higher in children who reported poor sleep 52 . Skipping breakfast was associated with total and abdominal obesity in adolescents independent of sleep duration 54 .…”
Section: <001 [A-bc][b-c]mentioning
confidence: 99%